La couleur dans l’environnement urbain - Luan Nguyen; Jacques Teller (Ambiances)
The aim of this paper is to present a user-oriented protocol for the characterization of colour attributes in an urban fragment. The challenge is to provide quantitative answers to these questions: how is colour organized? How does it develop a structure in the city? Our research investigates stable colour typologies. The obvious lack of effective tools for the chromatic assessment in the field of urban design was the main motivation of this research. The protocol is illustrated within the study of the “rue des Anglais” in Liège (Belgium) and the stability of the method is conducted through a series of validations.